2016
DOI: 10.1523/jneurosci.2962-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Maximally Regular Textures in Human Visual Cortex

Abstract: Here we expand on this work by investigating a class of textures that have maximal formal regularity, the 17 crystallographic wallpaper groups (Fedorov, 1891). We used texture stimuli from four of the groups that differ in the maximum order of rotation symmetry they contain, and measured neural responses in human participants using functional MRI and high-density EEG. We found that cortical area V3 has a parametric representation of the rotation symmetries in the textures that is not present in either V1 or V2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
157
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(186 citation statements)
references
References 92 publications
26
157
3
Order By: Relevance
“…One possibility is that the objects used in the current study lack the regularity in structure found in the textures generated by Simoncelli and colleagues 40 . Nevertheless, these findings fit with a recent study showing responses to different texture patterns could be differentiated in V3, but not in V2 41 .…”
Section: Discussionsupporting
confidence: 92%
“…One possibility is that the objects used in the current study lack the regularity in structure found in the textures generated by Simoncelli and colleagues 40 . Nevertheless, these findings fit with a recent study showing responses to different texture patterns could be differentiated in V3, but not in V2 41 .…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, subjective size perception, which involves the earliest stages of cortical visual processing35 and mental rotation, which may involve mid‐level visual processing (eg, V327, were not affected. Until recently, object recognition has not been well studied in PD.…”
Section: Discussionmentioning
confidence: 88%
“…Bertamini, Makin, and colleagues posit that the SPN is a fairly obligatory electrophysiological response that reflects the processing of symmetric stimuli, and other research has demonstrated that symmetry is an important feature extracted already early in the visual processing stream [16][17][18][19]. In the research by Jacobsen and Höfel, the posterior sustained negativity appeared to be task-dependent and/or driven by spontaneous processes.…”
Section: Discussionmentioning
confidence: 98%